Vincristine sulfate treatment influence on kidney function of female dogs with transmissible venereal tumor - Souza, Jessyca Vanderlei de Albuquerque; Gonçalves, Fernanda Danielle Maria; Lira-Junior, Arnaldo Cesar Oliveira Gomes; Escodro, Pierre Barnabé; Câmara, Diogo Ribeiro; Notomi, Marcia Kikuyo (Brazilian Journal of Veterinary Research and Animal Science, 2022)
Chemotherapy agents have some undesirable and non-selective cytostatic effects. Considering that kidneys are vulnerable to drug-induced toxicity, this study evaluated renal injury caused by vincristine sulfate (VS) in 12 female dogs diagnosed with transmissible venereal tumor (TVT). The animals were treated with VS (0.025 mg/kg IV) every 7 days for 4 weeks. During treatment, the animals were subjected to clinical examination, blood count, serum measurement of symmetric dimethylarginine (SDMA), blood urea nitrogen (BUN), creatinine, alanine aminotransferase, and alkaline phosphatase. In addition, urinalysis and urinary gamma-glutamyl transferase (GGT) measurements were performed. All parameters were determined three times: before beginning the treatment (T0), after 14 days (T1), and after 28 days (T2). During the study period, there were no changes in serum urea or creatinine levels, urine specific gravity, or persistent proteinuria. Furthermore, urinary GGT measurement did not indicate tubular lesions, and consistent elevation of SDMA was found in only one patient above the reference range. The results showed that weekly therapy with VS as a single agent for 28 days does not induce renal injury in most cases.